The One and the Many: Enduring Legacies of Spearman and Thurstone on Intelligence Test Score Interpretation. Issue 3 (3rd July 2019) - Beaujean, A. Alexander; Benson, Nicholas F.
ABSTRACT: Charles Spearman and L. L. Thurstone were pioneers in the field of intelligence. They not only developed methods to assess and understand intelligence, but also developed theories about its structure and function. Methodologically, their approaches were not that distinct, but their theories of intelligence were philosophically very different – and this difference is still seen in modern approaches to intellectual assessment. In this article, we describe their theories of intelligence and then trace how these theories have influenced the development and use of intelligence instruments, paying particular attention to score interpretation.